2020
DOI: 10.1101/2020.03.03.20030353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological and clinical features of 291 cases with coronavirus disease 2019 in areas adjacent to Hubei, China: a double-center observational study

Abstract: Lei, MD have contributed equally to this work.Word count: 3166 All rights reserved. No reuse allowed without permission. the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. AbstractBackground: The clinical outcomes of COVID-19 patients in Hubei and other areas are different. We aim to investigate the epidemiological and clinical characteristics of patient with COVID-19 in Hunan which is adjacent to Hubei. Methods:In this double-center, observational study, we recruited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 22 publications
3
48
0
3
Order By: Relevance
“…Second, we found that the majority of COVID-19 patients with CLD did not require admittance to the ICU, suggesting a less severe disease course in this subset of patients. Consistent with this finding, Chen et al reported that 13 out of 15 patients (86.7%) with both COVID-19 and CLD did not have severe disease [3]. Third, we found that many clinical reports regarding COVID-19 provided little or no information with respect to CLD.…”
Section: Researchsupporting
confidence: 90%
See 1 more Smart Citation
“…Second, we found that the majority of COVID-19 patients with CLD did not require admittance to the ICU, suggesting a less severe disease course in this subset of patients. Consistent with this finding, Chen et al reported that 13 out of 15 patients (86.7%) with both COVID-19 and CLD did not have severe disease [3]. Third, we found that many clinical reports regarding COVID-19 provided little or no information with respect to CLD.…”
Section: Researchsupporting
confidence: 90%
“…At the same time, identifying patients who are at risk of developing severe disease could help healthcare providers allocate their limited care resources more effectively in SARS-CoV-2infected communities. Previous retrospective studies reported an increased risk of developing more severe complications in COVID-19 patients with certain preexisting chronic diseases [2][3][4]. In addition, the development of acute organ damage and/or dysfunction has also been linked to increased severity and higher mortality rates among COVID-19 patients [2,[5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Initial database searches resulted in 1766 publications of potential relevance with 1000 identified via Google Scholar, 316 publications identified via Medline/PubMed, 324 publications identified via EMBASE, 89 publications identified via Web of Science, 34 publications identified via Wiley's Cochrane Library, and 3 publications identified via OpenGrey (Figure 1; Supporting Information Table S2) At the full article screening stage, 6 study authors were contacted by mail regarding possible unpublished data from their studies with 1 responding that the data were unavailable. After title/abstract review and full text article screening, 19 articles were included in the final meta‐analysis with a total of 1880 patients 27–45 (Figure 2 and Table 1). Eleven included studies were from peer reviewed journals 28,29,31,34–38,40,41,45 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two studies consistently demonstrated opposite associations between Type I interferon therapy and clinical outcomes, [30,33] when comparing summary statistics and other included studies. [28,29,31,34,35] Heterogeneity among populations studied may play a role in the disparate individual results, as half of these studies were conducted in China, one was conducted in Iran, five were conducted in Western Europe, and one was conducted in Cuba. Other irreconcilable factors that may have influenced patient outcomes included individual study exclusion criterion, as well as the dosage and delivery method of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of 3 sets of studies with 990, 454, and 1480 patients receiving Type I interferon therapy revealed that there were no significant associations between receiving Type I interferon therapy, compared to standard of care, and ICU admittance, requiring mechanical ventilation, or developing a severe or critical case of COVID-19, respectively (p>0.05; Figure 3B; Figure 3C; Figure 3D). [28][29][30][31][32][33][34][35][36] The analyses included 97, 167, and 537 control patients, respectively. The data exhibited very high heterogeneity in cases of ICU admittance and disease severity (both I 2 >90%), but relatively low in the case of mechanical ventilation (I 2 =12%).…”
Section: Effect Of Interferon Therapy On Clinical Outcomes In Covid-19mentioning
confidence: 99%